Transposon Mutagenesis of Planctomyces limnophilus and Analysis of a pckA Mutant - Schreier, Harold J. (American Society for Microbiology, 2012)
A Planctomyces limnophilus mutant generated using the EZ-Tn5 transposome was found to possess an insertion within pckA, encoding phosphoenolpyruvate carboxykinase. Disruption of pckA expression and elimination of enzymatic activity resulted in poor growth in glucose-free medium, demonstrating a gluconeogenic role for pckA in P. limnophilus.